ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK KONSTRUKSI GEDUNG PAMJAYA MENGGUNAKAN METODE HAZARD OF OPERABILITY STUDY (HAZOP) - Santika Sari; Rana Shalsabila (Dian Nuswantoro Semarang, 2021)
Over the past five years, work accident cases in Indonesia have continued to increase and reached the highest point in 2020 of 177,000 cases. This proves that steps are needed to reduce the number of work accidents by conducting a risk assessment in accordance with the main objective of K3, namely creating a safe work environment by conducting qualitative and quantitative assessments. This study aims to design a proposed improvement in the PAM JAYA building construction project by identifying the existing hazards and determining the level of risk using the Hazard of Operability Study method. The HAZOP method was chosen because its work is systematic, structured, thorough, and very suitable to be applied to the system newly implemented, in this study the PAM JAYA building construction project which has only been running for several months. This study finds 5 findings of extreme risk level hazards, 12 findings of highrisk level hazards, 2 findings of medium risk level hazards, and 1 finding of low risk level hazardsin the PAM JAYA building construction project. The suggestions for improvement given in this study are based on five hierarchies of risk control, such as Elimination, Substitution, Engineering, Administrative Control, and Use of PPE